Challenges of Special Education Teachers in Inclusive Mathematics Teaching in Primary Schools: A Preliminary Study - Mahmud, Muhammad Sofwan; Zainal, Mohd Syazwan; Pa, Wan Ahmad Munsif Wan (Angstrom Centre of Education, 2023)
Teaching and learning mathematics in an inclusive manner is growing, primarily to ensure that students with special needs receive equal education with mainstream students. Therefore, this study was carried out in order to identify the challenges that teachers face when implementing inclusive mathematics teaching in primary schools. This qualitative study employs a case study design with two outstanding special education teachers who are involved in inclusive education programmes in primary schools. Data collection method was done using semi-structured interviews and field notes. The data obtained were analyzed using the constant comparative analysis method to determine themes and sub-themes. The findings of the study found that special education teachers face various challenges in teaching mathematics in an inclusive manner, namely lack of pedagogical content knowledge to teaching mathematics in inclusive classrooms, dense classes, problems of subject teachers' attitudes and motivations, bullying problems between mainstream students and special needs students, and problems in ensuring effective communication in inclusive classes. This study expands the knowledge and literature about the challenges faced by special education teachers in primary schools in implementing inclusive teaching. Various initiatives must be taken to ensure that all challenges can be overcome and that inclusive mathematics teaching can be implemented effectively.